Amphiphilic biodegradable co-networks of Poly(butylene succinate)-Poly(ethylene glycol) chains for nano-gelation via Click chemistry and its potential dispersant for multi-walled carbon nanotubes. (September 2020) - Kertsomboon, Thanit; Chirachanchai, Suwabun
Abstract: Amphiphilic nanogel (APNG) is a class of material miscible with water and oil which is practical for active molecules incorporation, water-oil dispersion, etc. In general, preparation of APNGs requires multi-steps involving the copolymer with different hydrophilic units and the micelles formation to confine the nano-level for the crosslink. The present work proposes a simple way to prepare APNGs by applying the co-networks of biodegradable hydrophilic and hydrophobic chains. The co-networks between alkyno-poly(acrylic acid) (alkyno-PAA ) and diazido-poly(ethylene glycol) (N 3 -PEG-N 3 ) as well as diazido-poly(butylene succinate) (N 3 -PBS-N 3 ) via copper-catalyzed azide-alkyne cycloaddition (CuAAC) Click lead to APNG. The variation of hydrophilic N 3 -PEG-N 3 and hydrophobic N 3 -PBS-N 3 controls the amphiphilicity as evidenced from the swelling performances in various solvents with different polarity. The APNG obtained favors multi-walled carbon nanotubes (MWCNTs) to be dispersed in water for weeks without precipitation suggesting a potential dispersant of MWCNTs in hydrophilic media, especially aqueous solution. Graphical abstract: Image 1 Highlights: Amphiphilic nanogels (APNGs) under biodegradable and water soluble co-networked crosslinkers. Simple preparation of APNGs via CuAAC Click. Potential dispersant for multi-walled carbon nanotubes.